ЎЗБЕК ХАЛҚ ОҒЗАКИ ИЖОДИДА ҲАВОЛА БЎЛАКЛИ ЭРГАШГАН ҚЎШМА ГАПЛАР (Scientific journal of the Fergana State University, 2023)
The article describes the use of proverbs in a complex sentence with subordinate attributive pronouns, and discusses their types, means of preparation of complex proposals and their semantics.